Experimental data and thermodynamic modeling of the CO2 + Acetone + Efavirenz system at high pressures - de Souza, Guilherme Botelho Meireles; de Araujo, Paulo Cardozo Carvalho; Rocha, Helvécio Vinícius Antunes; Favareto, Rogerio; Freire, Nian Vieira; Arce, Pedro Felipe; Ferreira-Pinto, Leandro [UNESP]; Cardozo-Filho, Lucio [UNESP] (Elsevier, 2023)
It is important to understand the fluid phase behavior of the systems containing CO2, acetone, and Efavirenz for processes that use supercritical fluids to produce micro and/or nanoparticles for drug encapsulation. Thus, the purpose of this work is to measure experimentally data on the phase transitions of CO2 + Efavirenz and CO2 + acetone + Efavirenz systems using the visual static synthetic method and a variable-volume cell integrated into the experimental equipment. The experimental settings for the binary system were: pressures up to 16 MPa, temperatures of 333.15, 338.15, and 343.15 K, and the global Efavirenz mole fraction from 4 × 10−5 up to 15 × 10−5. The experimental settings for the ternary system were: pressure up to 10 MPa, temperatures from 303.15 to 333.15 K, and the global CO2 mole fraction from 0.2 up to 0.9. For the binary systems, the observed phase transitions are solid–fluid transitions; for the ternary systems, the observed phase transitions are bubble point (BP) transitions. Thermodynamic simulations using the Group Contribution Volume-Translated Peng-Robinson (GC-VT-PR) and Perturbed Chain Statistical Associating Fluid Theory (PC-SAFT) equations of state (EoS) demonstrated a striking correlation with experimental data. The relative deviations from pressure and temperature corroborate the efficiency of the thermodynamic models used in this work.
Keywords: Acetone; Efavirenz; Fluid Phase equilibrium; supercritical CO2